2013
DOI: 10.1177/1071100712470939
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Flexor Tendon Transfer for the Treatment of Severe Concomitant Peroneus Longus and Brevis Tendon Tears

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
1
37
1
Order By: Relevance
“…No studies were found with the primary focus on rehabilitation of surgically treated peroneal tendon tears or ruptures. Included studies described their rehabilitation method after one or more of the following surgical treatment methods: group A: primary repair with or without tubularization of the tendon, [ 1 , 2 , 6 , 7 , 12 14 , 19 , 23 – 28 , 31 , 36 , 39 , 43 , 47 50 , 53 , 56 , 61 , 62 , 65 , 69 ] group B: tenodesis, [ 1 , 2 , 4 , 5 , 10 , 14 , 16 , 25 , 30 , 40 , 43 , 44 , 46 , 47 , 49 , 50 , 61 , 62 , 67 , 69 ] group C: grafting [ 8 , 10 , 21 , 29 , 34 , 37 , 38 , 42 , 43 , 45 , 46 , 49 , 50 , 61 , 69 ] and group D: end-to-end suturing [ 1 , 29 , 41 , 43 , 47 , 66 , 68 ]. Fourteen studies reported two or more surgical treatment methods [ 10 , 25 , 29 , 43 , 4...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies were found with the primary focus on rehabilitation of surgically treated peroneal tendon tears or ruptures. Included studies described their rehabilitation method after one or more of the following surgical treatment methods: group A: primary repair with or without tubularization of the tendon, [ 1 , 2 , 6 , 7 , 12 14 , 19 , 23 – 28 , 31 , 36 , 39 , 43 , 47 50 , 53 , 56 , 61 , 62 , 65 , 69 ] group B: tenodesis, [ 1 , 2 , 4 , 5 , 10 , 14 , 16 , 25 , 30 , 40 , 43 , 44 , 46 , 47 , 49 , 50 , 61 , 62 , 67 , 69 ] group C: grafting [ 8 , 10 , 21 , 29 , 34 , 37 , 38 , 42 , 43 , 45 , 46 , 49 , 50 , 61 , 69 ] and group D: end-to-end suturing [ 1 , 29 , 41 , 43 , 47 , 66 , 68 ]. Fourteen studies reported two or more surgical treatment methods [ 10 , 25 , 29 , 43 , 4...…”
Section: Resultsmentioning
confidence: 99%
“…Rehabilitation after surgical treatment with grafting was reported in 16 studies [ 8 , 10 , 21 , 29 , 34 , 37 , 38 , 42 , 43 , 45 , 46 , 47 , 49 , 50 , 61 , 69 ] with a median immobilization period of 6.3 (range 3.0–13) weeks (Table 2 ). Of the studies ( n = 15) that reported on the start of ROM, 7 studies (47 %) reported on a start within 4 weeks post-operative [ 10 , 34 , 45 47 , 61 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only few case reports and retrospective series referring to the treatment of irreparable concomitant ruptures of peroneus longus and brevis tendons, a situation mimicking their segmental loss, were identified. Consequently, there are sparse treatment guidelines, which are limited to the use of autografts, allografts, tenodesis, or tendon transfers (Jockel & Brodsky, ; Squires et al, ; Stamatis & Karaoglanis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Debridement that results in extensive reduction of the tendon diameter also weakens it mechanically ( Figure 1F). 20,51 Tenodesis of the torn peroneal tendon to the intact one is the favored, and most common, solution because of the use of native tissue, rather than cadaver tissue, and the relative ease of the technique (Figures 1C and D). Once tenodesis is elected, the operative technique proceeds according to several key steps.…”
Section: Tenodesismentioning
confidence: 99%